The Effectiveness of Antifungal Emulgel Containing Ethanol Extract of Ketepeng Cina Leaves (Cassia alata L.) in Inhibiting the Growth of Dermatophyte Fungi - Alpha Christyananda Damar; Daniel Lantang; Rosye H.R. Tanjung (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
The leaves of Cassia alata L. (Ketepeng cina) are known to have antifungal properties and can be used to treat fungal skin infections such as tinea versicolor and ringworm. The leaf extract of Cassia alata contains antimicrobial compounds that inhibit fungal growth. The aim of this study was to determine the effectiveness of an antifungal emulgel containing ethanol extract of Cassia alata leaves in inhibiting the growth of dermatophyte fungi. This research was conducted from May to December 2024 at the Pharmacy Laboratory and Microbiology Laboratory of Cendrawasih University Jayapura. The plant samples were collected from Koya Barat, Jayapura City, and extracted using the maceration method with 96% ethanol. Phytochemical screening tests showed that Cassia alata leaves were positive for alkaloids, saponins, tannins, flavonoids, and phenols. The antifungal activity test of the ethanol extract emulgel formulation against Trichophyton rubrum, Microsporum canis, and Epidermophyton floccosum showed significance values lower than the commonly accepted level (α = 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Based on these findings, it can be concluded that the antifungal emulgel formulation containing ethanol extract of Cassia alata leaves is effective against Epidermophyton floccosum at a concentration of 1000.